THE NURSE OF THE FAMILY HEALTH STRATEGY AND THE CARE OF PATIENTS WITH PSYCHOLOGICAL DISTRESS - Araújo Souto, Darlene; Peres Fonseca, Rafaela; Ferreira da Silva Junior, Rene; de Almeida de Souza Torres, Silvério; Alves Barbosa Teles, Mariza; D’Paula Ribeiro Vieira Torres, Jaqueline; Souza Torres, Luana; Macedo da Costa, Lorendany; Marques Batista Rocha, Rodrigo; Gomes Campos Borel, Manuela; Thais Costa, Brunna; Maria Alencar, Ana; et al. (Health and Society, 2024)
The objective of this research is to understand nurses’ perception of care for patients with psychological distress in the Family Health Strategy (ESF). This is a qualitative and descriptive study. The study population was made up of seven nurses, working for more than six months at the ESF in Montes Claros - MG. The number of participants was defined by theoretical saturation. For data collection, a semi-structured interview was carried out. For data analysis, content analysis with thematic categorization was adopted. The research results showed that mental health care is provided casually by professionals in primary care. The difficulty of planning and executing actions involving new care practices and the multidisciplinary team was verified, and the obstacle is the lack of coordination with the network. The lack of training of professionals who deal with these patients was noted. It was observed that the nurse attributes an important role to the family in the patient’s adherence to therapeutic workshops. It is hoped that this study can contribute to increasing the quality of care for these patients and the need for scientific data, development of programs and other investigations related to this topic.